2018
DOI: 10.20944/preprints201804.0235.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Integrated Approach to Water-Energy Nexus in Shale-Gas Production

Abstract: ABSTRACT-Shale gas production is associated with significant usage of fresh water and discharge of wastewater. Consequently, there is a necessity to create the proper management strategies for water resources in shale gas production and to integrate conventional energy sources (e.g., shale gas) with renewables (e.g., solar energy). The objective of this study is to develop a design framework for integrating water and energy systems including multiple energy sources, cogeneration process, and desalination techn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…No multi-stage flash desalination units were included in this study. The reader is referred to several works that have treated this subject in detail [7,81,[81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: F: Thermal Energy For Water Desalinationmentioning
confidence: 99%
See 2 more Smart Citations
“…No multi-stage flash desalination units were included in this study. The reader is referred to several works that have treated this subject in detail [7,81,[81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: F: Thermal Energy For Water Desalinationmentioning
confidence: 99%
“…To illustrate, a recent study estimates that water withdrawals by electricity generating facilities in 2010 constituted 45% of the overall freshwater withdrawals in the United States with approximately 2% of that water being consumed as a result [4]. In addition to cooling purposes, large quantities of water are utilized in the extraction of raw fuels for electricity generation [7,8]. A recent study reported that the water consumption (in liters per gigajoule -L/GJ) for worldwide production of carbon-based and nuclear fuels is as follows: 1) traditional oil (3-7 L/GJ); 2) oil from oil sands (70-1800 L/GJ); 3) conventional natural gas (minimal water use); 4) shale gas (36-54 L/GJ); 5) coal (5-70 L/GJ); and 6) uranium (4-22 L/GJ) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 [87], which represents one of the significant Fig. 1 A hierarchical methodology of predicting DNI hotspots in the United States due to various activities of water-energy-food nexus [88] such as shale oil and gas production [89][90][91], agricultural production [92,93], etc. The solar data for San Antonio is obtained from the National Solar Radiation Data Base (NSRDB) between 1991 and 2010 are: hourly global solar irradiance, hourly direct solar irradiance, hourly diffuse solar irradiance, hourly solar incidence angle, hourly dry bulk temperature, hourly wet bulk temperature, and relative humidity.…”
Section: Site Description and Data Collectionmentioning
confidence: 99%